Long-term results of treatment for benign cervical epithelial changes associated with human papillomavirus - A. G. Kedrova; S. A. Levakov; M. D. Tsarenko (ABV-press, 2016)
A better understanding of the life cycle of human papillomaviruses (HPV) and innate immune control responses made it possible to lookfor ways of reducing the replication load of viral proteins and to activate the mechanisms of innate immunity for rapid viral elimination. This is extremely important since persistent infection mainly with papillomavirus types 16, 18, 35, 45, and 52 is the major cause of cervical cancer. Over 3 years, the screening program proposed by the World Health Organization in 2001 could reveal about 10 % of the 30 000 women who had moderate and severe or more cervical epithelial lesion and other 14 % had a HPV positive test showing mainly the presence of several strains. The level of persistent infection (the presence of one type of the virus within 12 months) was significantly higher among smokers and women older than 35 years of age. In our trial, the use of Isoprinosine in a dose of 50 mg/kg/day for 28 days contributed to rapid viral elimination persisting longer than 12 months in 91.8 % of the patients.